Utilizing type I interferon expression in the identification of antiphospholipid syndrome subsets. (3rd April 2021) - Cecchi, Irene; Radin, Massimo; Rodríguez-Carrio, Javier; Tambralli, Ajay; Knight, Jason S.; Sciascia, Savino
ABSTRACT: Introduction: Antiphospholipid Syndrome (APS) is a systemic autoimmune disease with a complex multifactorial pathogenesis, combining genetic background, traditional cardiovascular risk factors, disease-specific features such as the presence of antiphospholipid antibodies (aPL), and an imbalance of various immune system functions. Recent data support the role of interferons (IFNs), especially type IIFN (IFN-I), in the onset and development of APS clinical manifestations, including thrombotic events and obstetric complications. Areas covered: In this review, the authors aimed to discuss the growing body of evidence on the relevance of IFN-I pathways in APS, both from a basic mechanistic perspective, focusing on its possible use in disease/patients stratification. The IFN-I signature has shown promising, although preliminary, results in segregating aPL-positive subjects by aPL profile, association with other autoimmune conditions, such as lupus, age at onset, and current treatment, among others. Expert opinion: To date, the scarce available data as well as methodological and technical heterogeneity among studies limit the comparability of the results, thus requiring further validation to translate these findings to routine clinical practice. Therefore, further research is required in pursuit of more nuanced patient profiling and the development of new immunomodulatory therapeutic strategies for APS beyond anti-coagulant and antiplatelet agents.